The lonely silver rain - MacDonald, John D. (John Dann), 1916-1986 (MacDonald, John D. (John Dann), 1916-1986. Travis McGee series., 2013)
Someone linked to southern Florida's drug traffickers is trying to kill Travis McGee, and in order to save his own life, McGee must detonate a drug war.